Policy of State Protectionism in Countries with Various Level of Economic Development - M. Yu. Elsukov; B. Barsbold (Управленческое консультирование)
The article deals with the problems of forming a modern model of the state’s economic development. The characteristic of the content of protectionism as a model of state regulation of the economy is given. The origins of protectionism are considered. The experience of protectionist measures in Great Britain, Germany, the USA and Russia is considered. The rationale for applying the protectionist decisions of F. List, A. Hamilton, H. C. Carey, S. Witte is analyzed. The features of state protectionism in countries with developed and developing economies are demonstrated. The strengthening of protectionism in the behavior of modern states is due to various reasons. Various forms of protectionism appear because of the variety of public police tasks, methods and implementation. Protectionist intervention is seen as a temporary measure, as in the long term it deprives the economy of the potential for selfdevelopment, leads to a decrease in competitiveness, affects pricing and living standards of the population. One of the reasons for the spread of protectionism is the policy of transnational corporations. They seek to preserve the position they have won in the world economy, including through measures of protectionism. The choice of the protectionist model of economic growth in emerging economies is currently most influenced by the development trends of the world economy. These trends do not allow developing countries to rely on commodity models of economic growth. Modern protectionism can be considered as a definite paradigm of economic development. The main feature of modern protectionism (neoprotectionism) and its difference from classical protectionism consists not so much in the application of measures to protect the domestic producer, but rather in protecting the market, the state of which the consumer estimates. Protection in modern conditions continues to be significant, because the national economy will develop faster and more efficiently to adapt to the global economy with reasonable use of instruments for protecting national interests.